(3GdeUHGM GdRGgQ aj GdbQGAGJ GdYTQ GdLhGgQs - (3GdeHGQc Hf GdMSjf Hf CMeO Hf Ydj GdTgQRhQj GdHZOGOjs
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai aVGFd GdbQBf s
(3BNQgG (B:s
(3jfJgi HCKfGA GdbQGAGJ ai ShQI (B( (3de jcf (B) s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3JLhjO (B41) s
Keywords: (3GdbQGAGJ hGdJLhjOs